2022
DOI: 10.1080/02699931.2022.2043244
|View full text |Cite
|
Sign up to set email alerts
|

Emotional experiences in technology-mediated and in-person interactions: an experience-sampling study

Abstract: As the ubiquity of technology-mediated communication grows, so does the number of questions about the costs and benefits of replacing in-person interactions with technology-mediated ones.In the present study, we used a daily diary design to examine how people's emotional experiences vary across in-person, video-, phone-, and text-mediated interactions in day-to-day life. We hypothesized that individuals would report less positive affect and more negative affect after less life-like interactions (where in-perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
2
8
1
Order By: Relevance
“…In contrast, positive remote interactions were not associated with loneliness at the between-person level. In line with previous studies (e.g., Petrova & Schulz, 2022), it is possible that the nature of inperson interactions, which provide easily visible non-verbal behaviours, is a crucial piece of interaction quality that makes it more impactful on loneliness. Previous research also indicates that remote social interactions can have negative implications for well-being, such as passive social media use (e.g., scrolling without directly interacting with others) being associated with greater loneliness and lower well-being (Lou et al, 2012;Verduyn et al, 2017).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In contrast, positive remote interactions were not associated with loneliness at the between-person level. In line with previous studies (e.g., Petrova & Schulz, 2022), it is possible that the nature of inperson interactions, which provide easily visible non-verbal behaviours, is a crucial piece of interaction quality that makes it more impactful on loneliness. Previous research also indicates that remote social interactions can have negative implications for well-being, such as passive social media use (e.g., scrolling without directly interacting with others) being associated with greater loneliness and lower well-being (Lou et al, 2012;Verduyn et al, 2017).…”
Section: Discussionsupporting
confidence: 83%
“…Results from both experimental (Petrova & Schulz, 2022) and daily diary (Silva et al, 2023) studies indicate that face-to-face interactions may be more effective in reducing loneliness than remote (e.g., texting, video calls) interactions. These differences may be related to how in-person interactions can offer easily visible non-verbal behaviours, such as eye-contact (Petrova & Schulz, 2022;Silva et al, 2023) that may be harder/impossible to assess in digitally-mediated contexts. However, remote interactions may have a different impact on loneliness under conditions of wide-spread restrictions to in-person social interactions, such as during the COVID-19 pandemic (Towner et al, 2022).…”
Section: Within-and Between-person Associations Between Social Intera...mentioning
confidence: 99%
“…Interestingly, phone calls and video chats had no significant association with well-being. Petrova and Schulz 16 again used the COVID-19 pandemic situation to analyze the impact of different forms of communication (from most life-like communication, i.e., face-to-face to least life-like communication, i.e., text-based) onto well-being by using an ESM design. They found that the more life-like the communication was, the less lonely, less sad, more affectionate, more supported, and more happy people felt when compared to less life-like situation.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, individuals had to restrict FtF interactions because of the high risk of infection and were encouraged to increase their computer-mediated interactions (e.g., talking on the phone, videoconferencing, texting) in both private and professional contexts. Previous studies have suggested that FtF interactions are associated with higher well-being than computer-mediated interactions (Kroencke et al, 2023; Petrova & Schulz, 2022). This finding suggests that decreases in the proportion of FtF interactions may be related to lower well-being.…”
Section: Effects Of Extraversionmentioning
confidence: 89%